(untitled) (Fiep Bulletin - online, 2014)
This study will be based on the production of scientific knowledge in the area of ??Physical Education, and as a source of research, analyzes epistemological Gamboa performed by the University of Brasilia (1982), the State University of Campinas (Unicamp, 1997) and the Pontifical Catholic University of Campinas (1996), as well as the work done by Silva (1997). We identified the presence of four trends in research, in the southern region: 68.3% are research driven by trends Empirical-Analytical, 20.5% are research Phenomenological-Hermeneutic, 8.4% are Postmodern Studies and 2.8 % are research-Dialectical Critical. In the analyzes, evidenced the predominance of the Empirical-Analytic trends in all programs surveyed.